2020
DOI: 10.1016/j.jfluchem.2020.109593
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective transport of lithium across a supported liquid membrane

Abstract: Lithium extraction is a major concern in view of the increase in battery manufacturing. Separation of lithium from sodium is still challenging due to the similar chemical behavior of the two alkali metals. Sources such as brines or seawater usually contain large amounts of sodium which requires a high selectivity for the lithium extraction process. In this study, we demonstrate the application of a supported liquid membrane (SLM) with very high selectivity for the separation of lithium from sodium. A synergist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Organic solvent extractants applied by the mining and metallurgy industry typically contain multiple components, including an extractant (a metal chelating or binding reagent), a co-extractant (an adduct forming synergistic reagent), and a diluent (a bulk solvent). Example diluents are kerosene, xylene, and alkanes, such as dodecane [172,177,179,180,199]. Extractants include neutral species, such as ketones, beta-diketones, or ionizable species, such as organophosphates (Table 10).…”
Section: Multicomponent Solvent Systemsmentioning
confidence: 99%
“…Organic solvent extractants applied by the mining and metallurgy industry typically contain multiple components, including an extractant (a metal chelating or binding reagent), a co-extractant (an adduct forming synergistic reagent), and a diluent (a bulk solvent). Example diluents are kerosene, xylene, and alkanes, such as dodecane [172,177,179,180,199]. Extractants include neutral species, such as ketones, beta-diketones, or ionizable species, such as organophosphates (Table 10).…”
Section: Multicomponent Solvent Systemsmentioning
confidence: 99%
“…SLMs generally consist of an organic solvent (the LM phase) contained in the pores of a hydrophobic microfiltration membrane and kept there by capillary forces [ 71 ]. SLMs have been tested in the separation and recovery of various metal ions [ 72 , 73 , 74 , 75 ], anions [ 76 ], molecules of biological interest, and organics [ 65 , 77 , 78 ] from different aqueous media.…”
Section: Hmps Obtained By Coupling Membrane Processes With Solventmentioning
confidence: 99%
“…On this basis, the development of methods for selective recovery of lithium from lithium-rich brines represents an important research topic. Starting from this consideration, Zante et al [ 74 ] demonstrated the possibility to applicate a supported liquid membrane (SLM) for the separation of lithium from highly concentrated sodium solutions with very high selectivity. Among various acidic extracting agents, heptafluoro-dimethyloctanedione (HFDOD) was the most efficient when used in synergistic combination with tri-n-octylphosphine oxide (TOPO) diluted in dodecane.…”
Section: Hmps Obtained By Coupling Membrane Processes With Solventmentioning
confidence: 99%
See 2 more Smart Citations